The Present and Future of Audio Description and Subtitling for the Deaf and Hard of Hearing in Spain - Utray, Francisco; Pereira, Ana; Orero, Pilar (Meta, 2009)
AbstractThe aim of this article is to describe the state of the art in Spain of the two most popular media accessible modalities: audio description and subtitling for the deaf and hard of hearing. The article traces their origin and development up to the present time. It also examines standards and laws and analyses the economic and operative implications of media accessibility, which does not follow traditional economic parameters. The article aims to define the profile of future describers and subtitlers in Spain, who are currently being trained in the field of Audiovisual Translation. It concludes by proposing a wide variety of measures to be taken in order to reach full media accessibility and raise popular awareness of these services which are available now and will be increasingly so in the future with the change from analogous to digital broadcasting.